Mutation at Different Sites of Metal Transporter Gene OsNramp5 Affects Cd Accumulation and Related Agronomic Traits in Rice (Oryza sativa L.) - Wang, Tiankang; Li, Yixing; Fu, Yuefeng; Xie, Hongjun; Song, Shufeng; Qiu, Mudan; Wen, Jiong; Chen, Muwen; Chen, Ge; Tian, Yan; Li, Chengxia; Yuan, Dingyang; et al. (Frontiers in Plant Science, 2019)
OsNramp5 is a key gene involved in the control of the uptake of Cd, Mn, and other metal ions by rice root cells. The functional deficiency of this gene can significantly reduce the accumulation of Cd in rice grains, but the effects of its mutation on agronomic traits such as yield and quality have not been investigated comprehensively yet. In the present study, three Huanghuazhan-based OsNramp5 mutants[LCH1(Low Cadmium Huanghuazhan 1), LCH2(Low Cadmium Huanghuazhan 2), and LCH3(Low Cadmium Huanghuazhan 3) ]were obtained using CRISPR/Cas9(Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated Proteins9) technology. The mutation type analysis showed that LCH1, LCH2, and LCH3 encoded defective OsNramp5 protein sequences containing only 76aa, 176aa, or 266aa, respectively. The determination of metal content and the statistics of related agronomic traits revealed that the functional deficiency OsNramp5 not only significantly reduced the accumulation of Cd in the grains of the mutants, but also affected rice yield and quality. However, with the decrease of OsNramp5 mutation degree, its effects on chlorenchyma Mn accumulation, yield and quality were also diminished. Additionally, we also found that the increase in the concentration of Mn in the soil restored the phenotype of the declined yield and quality due to the functional deficiency of OsNramp5. Our findings provide novel insights into and new materials for breeding rice varieties with low Cd accumulation and excellent agronomic traits under severe Cd pollution environment.